2007
DOI: 10.1158/0008-5472.can-07-5755
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 Interacts with the p85 Subunit of Phosphatidylinositol 3-Kinase to Regulate Cell Adhesion and Motility

Abstract: Cell migration plays an important role in tumor cell invasion and metastasis. Previously, we reported that caspase-8 contributes to cell migration and adhesion, a novel nonapoptotic function of an established apoptotic factor. Herein, we report that pro-caspase-8 is capable of restoring cell migration/ adhesion to caspase-8-null cells, establishing the first biological function of a pro-caspase. The catalytic activity of caspase-8 was not required for cell motility. Stimulation of motility with epidermal growt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 18 publications
8
120
1
Order By: Relevance
“…26 Caspase 8 also seems to play a role in cell adhesion and motility. 27 In our study, we found definitive evidence that caspases are at the crux of both TRAIL-induced apoptosis and proliferation of RA FLS, as a pan-caspase inhibitor blocked both cellular responses. The use of specific caspase inhibitors suggested an involvement of caspases 3, 8 and 9 in TRAIL-induced apoptosis, and of caspases 3 and 8 in TRAIL-induced proliferation.…”
supporting
confidence: 62%
“…26 Caspase 8 also seems to play a role in cell adhesion and motility. 27 In our study, we found definitive evidence that caspases are at the crux of both TRAIL-induced apoptosis and proliferation of RA FLS, as a pan-caspase inhibitor blocked both cellular responses. The use of specific caspase inhibitors suggested an involvement of caspases 3, 8 and 9 in TRAIL-induced apoptosis, and of caspases 3 and 8 in TRAIL-induced proliferation.…”
supporting
confidence: 62%
“…Fas) or other proteins in the death receptor pathways (e.g. caspase-8 and Fas-associated death domain) promotes tumor formation, growth, invasion, and even metastasis (45)(46)(47)(48)(49)(50)(51)(52). Thus, it is also possible that Ras-induced DR5 expression is involved in promoting Ras-mediated oncogenesis and/or metastasis, particularly under apoptosis-compromised conditions.…”
Section: Discussionmentioning
confidence: 99%
“…So, in NB7 neuroblastoma cells with hyperactive Src or stimulated with EGF, caspase-8 becomes phosphorylated on Y380 enabling the protein to bind the p85 subunit of PI3K and to activate the PI3K effector Rac, which is of pivotal relevance for cell migration. 29,30 In this model of cell migration, the enzymatic activity of caspase-8 is again dispensable. 29,30 In the same cellular model, a non-catalytic function of caspase-8 in Src-dependent cell adhesion and activation of extracellular-regulated kinase 1/2 has also been shown, but the relation of these events to p85/Rac-mediated cell migration is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In this model of cell migration, the enzymatic activity of caspase-8 is again dispensable. 29,30 In the same cellular model, a non-catalytic function of caspase-8 in Src-dependent cell adhesion and activation of extracellular-regulated kinase 1/2 has also been shown, but the relation of these events to p85/Rac-mediated cell migration is still unclear. 31 In addition, caspase-8 has also been found to be recruited to the focal adhesion complex in NB7 cells in which it enhances cell migration by stimulating talin cleavage by calpains in a caspase-activity/apoptosisindependent manner.…”
Section: Discussionmentioning
confidence: 99%